Genetic requirements for infection-specific responses in conferring disease resistance in Arabidopsis - Yoo, Sung-Je; Choi, Hyo Ju; Noh, Seong Woo; Cecchini, Nicolás M.; Greenberg, Jean T.; Jung, Ho Won (Frontiers in Plant Science, 2022)
Immunity in plants arises from defense regulatory circuits that can be conceptualized as modules. Both the types (and isolates) of pathogen and the repertoire of plant receptors may cause different modules to be activated and affect the magnitude of activation. Two major defense enzymes of Arabidopsis are ALD1 and ICS1/SID2. ALD1 is an aminotransferase needed for producing the metabolites pipecolic acid, hydroxy-pipecolic acid, and possibly other defense signals. ICS1/SID2 produces isochorismate, an intermediate in the synthesis of salicylic acid (SA) and SA-derivatives. Metabolites resulting from the activation of these enzymes are found in petiole exudates and may serve as priming signals for systemic disease resistance in Arabidopsis. Mutants lacking ALD1 are known to have reduced SA accumulation. To further investigate the role of ALD1 in relation to the SA-related module, immunity phenotypes of double mutants that disrupt ALD1 and ICS1/SID2 or SA perception by NPR1 were compared with each single mutant after infection by different Pseudomonas strains. Exudates collected from these mutants after infection were also evaluated for their ability to confer disease resistance when applied to wild-type plants. During infection with virulent or attenuated strains, the loss of ALD1 does not increase the susceptibility of npr1 or sid2 mutants, suggesting the main role of ALD1 in this context is in amplifying the SA-related module. In contrast, after an infection that leads to strong pathogen recognition via the cytoplasmic immune receptor RPS2, ALD1 acts additively with both NPR1 and ICS1/SID2 to suppress pathogen growth. The additive effects are observed in early basal defense responses as well as SA-related events. Thus, there are specific conditions that dictate whether the modules independently contribute to immunity to provide additive protection during infection. In the exudate experiments, intact NPR1 and ICS1/SID2, but not ALD1 in the donor plants were needed for conferring immunity. Mixing exudates showed that loss of SID2 yields exudates that suppress active exudates from wild-type or ald1 plants. This indicates that ICS1/SID2 may not only lead to positive defense signals, but also prevent a suppressive signal(s).